Skala TAI-G Untuk Kecemasan Menghadapi Ujian Pada Siswa Sekolah Menengah Atas - Nayu, Hasnaa' Zahuna (Jurnal VARIDIKA, 2020)
Anxiety facing exams refers to the student's tendency to understand evaluativ situations where their performance will be assessed, such as high-risk exams, as they are very threatening. The threat here is their self-esteem, fear will be judged negatively by teachers, friends, or parents.  The purpose of this research is to seek the validity and reliability of the TAI-G scale. This research uses a quantitative approach. The number of samples of this study was 101 SMA/SMK students in Magelang with an age range of 15-17 years. Sampling in this study used simple random sampling techniques. The results of the analysis show 21 items declared valid with a correlation of item-Total 0.25, 1 invalid item with a total-item correlation of 0.25, and an alpha reliability of 0.907.